Em luta pelo mais sagrado dos direitos : identidades políticas, ideologias e práticas eleitorais das monarquias constitucionais bragantinas à luz do fenômeno liberal (1820-1847) - Evaristo Caixeta Pimenta (2022)
The processes of implementation of liberal political orders characterized the political lives of Portugal and Brazil during the first half of the 19th century. This thesis approaches this issue through a comparative perspective and in the light of a discussion about the liberal phenomenon, whose foundations date back to the previous century. The objective of this work is, therefore, to analyze, in an integrated way, the repercussions of the transition from the traditional power to the rule of law, in a enlightened framework, starting at the transnational macroscale and getting through to the microscale of the electoral spaces related to the bragantine constitutional monarchies, during the 1840s. In this way, it seeks to bring to light the stories of interactions between Portuguese and Brazilian voters and the political ideologies that aimed to establish new asymmetries of power in a context prior to the advent of political parties.